Integrated Postsecondary Education Data System (IPEDS): Fall Enrollment, 1987 ([Verlag nicht ermittelbar], 1999)
The Fall Enrollment survey is conducted annually by the National Center for Education Statistics (NCES) as part of the Integrated Postsecondary Education Data System (IPEDS). The survey collects student enrollment data by 11 age categories as defined by the Office for Civil Rights (OCR). There are three parts included in this survey. Part A, Enrollment Summary, provides enrollment data by total of men and women and by level and year of study of the student. Part B, Enrollment Summary of Students by Age, comprises all students enrolled for credit by level of study and by sex and age of student. Part C, Clarifying Questions, supplies information on students enrolled in remedial courses, extension divisions, and branches of schools, as well as numbers of transfer students from in-state, out of state, and other countries. There are 268,567 total records in this data file.